PECULIARITIES OF THE FEED TEMPERATURE CHANGING ALONG THE MILL 320 UNE OF RUP "BMZ" AT ROLLING OF REINFORCING PROFILES BY MEANS OF ROLLING-AND-SEPARATION - S. M. Zhuchkov; V. A. Matochkin; D. N. Andrianov; M. A. Murikov; M. I. Titov; D. G. Palamarj; A. I. Leshchenko (Литьë и металлургия, 2006)
The peculiarities of the temperature changing of the roll along the length of mill at using of new technological schema of production of reinforce rolled metal of small cuts in conditions of RUP are considered.